Implementasi Ajaran Yoga Kapamangkuan Di Pasraman Mulat Sarira Desa Adat Duda Desa Duda Timur Kecamatan Selat Kabupaten Karangasem - I Wayan Nerta (Jurnal Penelitian Agama Hindu, 2021)
Kapamankuan yoga teachings are part of the implementation of tantric yoga teachings for Pamangku, namely an implementation of yoga teachings that are closely related to sādhāna. My uncle does not only need to be physically fit or physically fit but also mentally and spiritually healthy. Pamangku in his duties nganteb upakara there are steps that are carried out both physically and mentally. Parts of body posture such as the masila den apened sitting position, ngunda bayu or prānāyāma techniques, hand movements (mudras) and mantras or seha are part of the yoga attitude, namely the Kapamangkuan yoga teachings. The Mulat Sarira Pasraman, which is located in the Duda Traditional Village, is a place for deepening the teachings of Hinduism, one of which is the study of Kapamankuan teachings. Departing from this, it is necessary to conduct research, namely: Implementation of Kapamankuan Yoga Teachings, at the Mulat Sarira Pasraman, Duda Traditional Village, East Duda Village, Selat District, Karangasem Regency. Based on this, the problem formulated as follows: The teachings of Kapamangkuan Yoga, what is taught at the Mulat Sarira Pasraman? This study uses a qualitative method with the aim of analyzing the implementation of Kapamankuan yoga teachings at the Mulat Sarira Pasraman. The data from this study were obtained through observation, interviews and document studies. The collected data was verified and then analyzed by Structural Functional theory. The results of the research are the Kapamangkuan Yoga Teachings taught in the activities at the Mulat Sarira Pasraman, namely the Kapamangkuan sesana, the postures of the sitting asana masila pened, the ngunda bayu or prānāyāma breathing arrangements, and the hand gestures or mudras and mantras. As for the findings of this study is the connection between the physical and social body with mental and spiritual awareness. The existence of a social conception of "Kalingsiran" and Pamangku is referred to as a functional position "Jero Mangku," which has dimensions of kapamankuan status. The award given by the community to the title "Jero Mangku" is a specific profession as a liaison that bridges public awareness / Hindus with the abstract realm